Benjamin's Theory of the Lyric - David E. Wellbery (Studies in 20th & 21st Century Literature, 1986)
The paper reconstructs the argument of Benjamin's early Hölderlin essay, with special emphasis on the notion of das Gedichtete. This notion is shown to name a fundamental dissonance between two semiotic modalities, graphics and Gestalt.
Keywords: Hölderlin; Walter Benjamin; poetic language; lyric; das Gedichtete; graphics; Gestalt